Combat Radiology Diagnostic Imaging of Blast and Ballistic Injuries - Folio, Les.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Combat Radiology provides unique insights into a military radiologist$1 (Bs role in the modern battlefield environment. Drawing on his recent experiences in Iraq, Col. Les Folio, a retired air force radiologist and flight surgeon with over twenty years of service, presents a comprehensive introduction to diagnostic imaging technology for the deployed military physician. Topics in the book include descriptions of imaging capabilities of hospitals in deployed military bases in combat zones; practical imaging techniques and terminology associated with penetrating/perforating blast and ballistic injuries; recent medical advances on the battlefield; and the changing role of imaging modalities in combat situations. Additionally, specific anatomic and pathologic imaging cases from combat situations are presented, including traumatic brain injury, chest, abdomen/pelvis, and skeletal trauma. Combat Radiology will appeal not only to military radiologists and surgeons, but also to civilian emergency radiologists and trauma physicians who encounter patients with ballistic and blast injuries resulting from armed conflict, terrorism, and disaster situations.s
The Combat Environment: Preparation for Deployment -- Echelons of Combat Casualty Care and Associated Imaging Resources -- Blast and Ballistics: Types, Background, Terminology -- to Imaging of Penetrating/Perforating Blast and Ballistic Injuries -- Significant Medical Advances on the Battlefield and the Changing Roles of Imaging -- Imaging Thresholds of Salvageability of Life, Limb, and Eyesight -- Imaging Traumatic Brain Injury On and Off the Battlefield -- Chest Imaging in a Battlefield Hospital -- Abdomen and Pelvis Imaging in Iraq -- Skeletal Trauma in Iraq.
Keywords: Medicine; Radiology, Medical; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology